2016
DOI: 10.1038/npp.2016.232
|View full text |Cite|
|
Sign up to set email alerts
|

A Single Dose, Randomized, Controlled Proof-Of-Mechanism Study of a Novel Vasopressin 1a Receptor Antagonist (RG7713) in High-Functioning Adults with Autism Spectrum Disorder

Abstract: The core symptoms of autism spectrum disorder (ASD) include impaired social communication, repetitive behaviors, and restricted interests. No effective pharmacotherapy for these core deficits exists. Within the domain of social communication, the vasopressin system is implicated in social cognition and social signaling deficits of ASD, and represents a potential therapeutic target. We assessed the effects of a single 20 mg intravenous dose of the arginine vasopressin receptor 1A (V1a) antagonist, RG7713, on ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 61 publications
0
60
3
1
Order By: Relevance
“…The data for this report are derived from two studies conducted at the same three academic centers in the United States: (a) A multicenter, observational study (http://clinicaltrials.gov: NCT01669889); and (b) an interventional study [http://clinicaltrials.gov: NCT01474278; Umbricht et al, ], for which the data included in this analysis were collected at baseline, prior to any drug administration. In both studies, identical exploratory assessments were administered in the same order.…”
Section: Methodsmentioning
confidence: 99%
“…The data for this report are derived from two studies conducted at the same three academic centers in the United States: (a) A multicenter, observational study (http://clinicaltrials.gov: NCT01669889); and (b) an interventional study [http://clinicaltrials.gov: NCT01474278; Umbricht et al, ], for which the data included in this analysis were collected at baseline, prior to any drug administration. In both studies, identical exploratory assessments were administered in the same order.…”
Section: Methodsmentioning
confidence: 99%
“…A recent Autism Speaks sponsored working group panel recommended the Vineland‐II as suitable (having adequate reliability, validity, and responsiveness) to quantify social communication deficits in clinical trials of ASD [Anagnostou et al, ; see also McConachie et al, ]. The Vineland‐II is also increasingly used in randomized trials targeting core ASD symptoms and/or adaptive behavior more broadly [e.g., Chugani et al, ; Dawson et al, ; Hardan et al, ; Scahill et al, ; Umbricht et al, ; Veenstra‐VanderWeele et al, ; Ventola et al, ], in part due to the relative lack of other reliable measures of change in these behaviors [Anagnostou et al, ]. This increasing use may also reflect the relatively broader scope of adaptive behaviors assessed by Vineland‐II, relative to the more circumscribed set of core ASD symptoms (McDougall et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…The predicted pharmacokinetics and pharmacodynamics of V1a antagonists were suitable for humans, however not for rodents. Trials in humans with social deficits associated with autism have shown promising results …”
Section: Figurementioning
confidence: 99%
“…The 2017 Frontiers in Medicinal Chemistry (FiMC) conference, organizedj ointly by the GermanC hemical Society (GDCh;K arl-Heinz Baringhaus), the German Pharmaceutical Society( DPhG; Christa E. Müller), and the Division of Medicinal Chemistry and Chemical Biology of the Swiss Chemical Society (SCG;Y ves Auberson,J ean-Louis Reymond), was held at the Department of Chemistry and Biochemistry of the University of Bern, February [12][13][14][15]2017. While this conference has taken place every year since 2004 in ad ifferent city in Germany,t his year it was held in Switzerlandf or the first time.…”
mentioning
confidence: 99%
See 1 more Smart Citation